Synthesis and Characterization of Electrospun Edible Bird’s Nest/Polyvinylpyrrolidone Nanofibers - Hapidin, Dian Ahmad; Priyanto, Aan; Eka Sentia Ayu Listari; Dhewa Edikresnha; Khairurrijal, Khairurrijal (Greensusmater, 2025)
Edible Bird's nest (EBN) is a highly valuable food product due to its rich nutritional content and potential health benefits. In this study, we investigated the morphology and diameter of electrospun EBN/PVP nanofibers by exploring different solution and electrospinning parameters. Smooth, homogeneous, and defect-free nanofibers were obtained using EBN:PVP ratios ranging from 10:90 to 60:40. Increasing the concentration of EBN in the solution resulted in fibers with larger diameters. The fiber diameter was found to decrease with increasing voltage of the electrospinning process. In addition, increasing the needle-to-collector distance resulted in fibers with smaller diameters. The FTIR spectrum of EBN/PVP showed a combination of the spectral characteristics of both components. The EBN/PVP nanofiber blend showed improved thermal stability, probably due to the interaction between EBN and PVP, which strengthened the blend structure. EBN/PVP nanofibers with dominant EBN content can be very useful as a matrix to protect bioactive ingredients from environmental degradation while allowing controlled release.